The relationship between the stocks performances of selected financial sector in main board towards Kuala Lumpur composite index / Siti Noraini Mahmud (Faculty of Business and Management, 2008)
This study had used 10 out of 40 stocks under the selected financial sectors in analyzing theperformance of stock listed in KLCI main board. To see the performance of the stocks, the researcher had analyzed the relationship between stock prices of selected finance sectors in Main Board through the SPSS Program. The result showed that the price of the stocks had all significant relationships on the stock performance. The price for the stocks had dropped dramatically during the increase of the oil prices and this lead to the lower return during that time. However the percentage increased or decreased in stock return due to the changed in stock price during that five years study. The investments tend to be more risky during the period of December 2007 until know. This is because any 1% change in stock price will lead to higher amount of changed in KLCI and vice versa.